2011
DOI: 10.1177/0091270010366445
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Effect of Rifampin on the Pharmacokinetics of Linezolid: In Silico and In Vitro Approaches to Explain Its Mechanism

Abstract: The effect of rifampin on the steady-state pharmacokinetics of linezolid was evaluated in an open-label, multiple-dose, crossover study in 16 healthy subjects. When coadministered with rifampin, area under the plasma concentration-time curve over the dosing interval and maximum concentration values for linezolid were reduced approximately 32% and 21%, respectively. Time to maximum concentration and apparent volume of distribution were generally similar between treatments. The mean half-life and apparent oral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 24 publications
2
63
3
1
Order By: Relevance
“…Additionally, there was no inhibitory effect on P-gp even at a concentration of 500 M in both the in vitro screening and P-gp-expressing MDCK cells (see Table S4 in the supplemental material). These results support a previous report using human primary hepatocytes (52). We also assessed the effect of LZD on CYP2B6 using an in vitro screening kit, but no inhibition was observed at 500 M (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, there was no inhibitory effect on P-gp even at a concentration of 500 M in both the in vitro screening and P-gp-expressing MDCK cells (see Table S4 in the supplemental material). These results support a previous report using human primary hepatocytes (52). We also assessed the effect of LZD on CYP2B6 using an in vitro screening kit, but no inhibition was observed at 500 M (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…Rifampicin, a well-known inducer of P-glycoprotein and cytochrome P450 enzymes, decreases linezolid serum levels in critically ill patients [25]. Another study confirmed this finding in healthy volunteers [26,27]. GEBHART et al [25] suggest the interaction to be mediated by Pglycoprotein, since an in vitro study has shown that linezolid is not metabolised by cytochrome P450 enzymes [28].…”
Section: Discussionmentioning
confidence: 91%
“…P-glycoprotein polymorphism could explain some of the interpatient variation that we observed. However, in a recent study GANDELMAN et al [27] refer to unpublished data on file from Pfizer suggesting that linezolid is not a P-glycoprotein substrate. Their hypothesis for the observed interaction between linezolid and rifampicin is that a large increase in expression of CYP3A, which typically has a small contribution (0.7-10.5%) to linezolid clearance, could cause a small decrease in linezolid exposure [27].…”
Section: Discussionmentioning
confidence: 99%
“…The mean (SD) durations of linezolid treatment were 77.5 (31.9) and 84. 4 (6). Therefore, use of this combination requires increasing the linezolid dosages in order to obtain the pharmacodynamic parameter that predicts the efficacy of linezolid (AUC/MIC Ͼ 80).…”
Section: Discussionmentioning
confidence: 99%